Beilschmiedia bidoupensis (Lauraceae), a new species from Bidoup-Nui Ba National Park, southern highland of Vietnam - Komada, Natsuki (2023)
Beilschmiedia bidoupensis (Lauraceae) is described from Bidoup-Nui Ba National Park in the southern highland of Vietnam. The new species is characterized by lanceolate terminal buds that are ca. 2.5 mm long without coriaceous scales and covered with whitish brown hairs, glabrous twigs, predominantly alternate leaves evenly arranged on branches, elliptic leaf blade with acuminate apex, and depressed globose to transversely ellipsoidal fruits with not verrucose but asperously furfuraceous surface. A description, illustrations, preliminary conservation assessment, and DNA barcodes of ITS, psbA-trnH and trnL regions, are provided.